2008
DOI: 10.1186/1471-213x-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Pax7 is requisite for maintenance of a subpopulation of superior collicular neurons and shows a diverging expression pattern to Pax3 during superior collicular development

Abstract: Background: Pax7 encodes a transcription factor well-established as an important determinant of mesencephalic identity and superior collicular development. Pax7 mutant mice, however, present with no obvious morphological impairments to the superior colliculus. This finding is paradoxical and has been attributed to functional redundancy afforded by its paralogue Pax3. Here we utilise Pax7 mutant mice to investigate the precise role of this important developmental regulator during superior collicular development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 54 publications
0
42
0
3
Order By: Relevance
“…For example, Pax6 is expressed in the differentiating neural cells of the optic vesicles (Stoykova and Gruss, 1994) in response to local signals from the overlying ectoderm (Bailey et al, 2004), while Pax7 expression continues in dorsal tectal/collicular neurons (Jostes et al, 1990;Kawakami et al, 1997;Thompson et al, 2004Thompson et al, , 2007Thompson et al, , 2008Thomas et al, 2007) and Pax3 is found in Bergmann glia and cells surrounding the Purkinje cells (Stoykova and Gruss, 1994).…”
Section: Pax Expression During Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Pax6 is expressed in the differentiating neural cells of the optic vesicles (Stoykova and Gruss, 1994) in response to local signals from the overlying ectoderm (Bailey et al, 2004), while Pax7 expression continues in dorsal tectal/collicular neurons (Jostes et al, 1990;Kawakami et al, 1997;Thompson et al, 2004Thompson et al, , 2007Thompson et al, , 2008Thomas et al, 2007) and Pax3 is found in Bergmann glia and cells surrounding the Purkinje cells (Stoykova and Gruss, 1994).…”
Section: Pax Expression During Developmentmentioning
confidence: 99%
“…Spleen, bone marrow Speculate tumor suppressor activity (Kaneko et al, 1998) (Stoykova and Gruss, 1994) Midbrain Superior collicular neurons Not specified (Thompson et al, 2004(Thompson et al, , 2007(Thompson et al, , 2008 Chicken Brain *Tectal neurons *Nuclei of Thalamus/Pons/ Midbrain Speculate maintenance of normal physiology (Shin et al, 2003) Cerebellar Bergmann glia…”
Section: Pag Of Midbrain Medulla Oblongata Caudal Nucleus Smooth Muscmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation of Pax genes by gene mutation, gene misexpression or tissue transplantation has highlighted the ability of Pax genes to alter key developmental processes (Gehring, 1996;Mansouri et al 1996;Nomura et al 1998;Matsunaga et al 2000). Pax7 in particular is known to be functionally significant during midbrain development (Thompson et al 2008) and is up-regulated in the injured adult CNS (Kawakami et al 1997;Nomura et al 1998;Thomas et al 2007), thus we sought to investigate whether it was important in optimizing cell survival and graft integration.…”
Section: Introductionmentioning
confidence: 99%
“…Amphibians, birds and mammals have one Pax3 and one Pax7 gene, whereas there were two Pax3 and two Pax7 in zebrafish, which has a two round genome duplication during its evolution (Thompson et al, 2008). Alternative splicing variants of Pax3 and Pax7 have been identified in human, mouse, zebrafish and salmon, although their specific distribution and function remain poorly understood (Vogan et al, 1996;Ziman et al, 1997;Seo et al, 1998;Barber et al, 1999;Gotensparre et al, 2006).…”
Section: Introductionmentioning
confidence: 98%